The Influence of Previous Year’s Audit Opinion and Operational Complexity on Audit Report Lag with the Audit Committee as a Moderating Variable - Putri Ekawati; Dea Annisa (Scieclouds Publishing, 2026)
This study aims to examine the effect of the prior year's audit opinion and operational complexity on audit report lag, with the audit committee as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This study uses a quantitative approach with an associative method. The type of data used in this study is secondary data obtained from the companies' financial statements. The analytical method used in this study is panel data regression. Data analysis was performed using EViews 12 software and Microsoft Excel. The population in this study was energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research sample was determined using a purposive sampling method based on predetermined criteria, totaling 54 companies over the five years of the study, resulting in a sample size of 270. The results show that the prior year's audit opinion and operational complexity have no effect on audit report lag. Furthermore, the audit committee cannot moderate the effect of the prior year's audit opinion on audit report lag. The audit committee also cannot moderate the effect of operational complexity on audit report lag.